Understanding the various evolutionary stages of the low-mass star-formation process by SO and SO2 - Ghosh, Rana; Das, Ankan; Gorai, Prasanta; Mondal, Suman Kumar; Furuya, Kenji; Tanaka, Kei E. I.; Shimonishi, Takashi (Frontiers in Astronomy and Space Sciences, 2024)
SO and SO2 are two potential candidates to trace the different evolutionary phases of the low-mass star-formation process. Here, we report observations of SO and SO2 along with their isotopologues, 34SO and 34SO2, respectively, in four distinct phases of the low-mass star-formation process (prestellar core, first hydrostatic core, Class 0, and Class I) with an unbiased survey carried out using the Institut de Radioastronomie Millimetrique (IRAM) 30 m telescope. Interestingly, the estimated abundances of SO and SO2 show an increasing trend from the prestellar phase to the Class 0 stage and then a decrease in the Class I phase. A similar trend is obtained for OCS and H2S. In contrast, the obtained SO/SO2 ratio decreases gradually from the prestellar core to the Class I stage. We have used the three-phase Rokko chemical code to explain our observations. The modeled abundances of SO and SO2 exhibit an increase within the inner region as the cold gas transforms into a hot gas. The modeled abundance ratio of SO to SO2 exhibits a notably high value in cold gas environments. This ratio decreases to less than 1 within the temperature range of 100–300 K and then increases to approximately 1 beyond 300 K. In the outer region, the simulated ratio consistently exceeds the value of 1. Our work is an observational testbed for modeling the chemistry of SO/SO2 during low-mass star formation. However, our findings may require more sample sources with higher resolution and a more robust model for validation.